OPTIMALISASI PERAN KEPEMIMPINAN CAMAT UNTUK MENINGKATKAN KINERJA PEGAWAI DALAM MENINGKATKAN PELAYANAN PUBLIK DI KECAMATAN (STUDI KASUS KANTOR KECAMATAN GEBANG KABUPATEN LANGKAT SUMATERA UTARA) - Sianturi, Faldo Junayles; Rajagukguk, Jonson; Panjaitan, Maringan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to examine and analyze the role of sub-district leadership (Camat) in improving employee performance and optimizing public service delivery at the Gebang Sub-district Office, Langkat Regency. In the context of regional governance, the Camat plays a strategic role as the extension of the regency/city government, tasked with coordinating administration, community empowerment, and public services at the sub-district level. This research employs a qualitative approach, utilizing interviews, observations, and documentation as data collection techniques. The results of the study indicate that the Camat of Gebang applies a participative and transformational leadership style through open communication strategies, task delegation based on employee competence, and a humanistic and exemplary supervisory approach. These strategies effectively enhance employee discipline, motivation, and work quality, which directly contribute to improved public service performance. Nevertheless, several challenges remain, such as limited human resources, underutilization of technology, and a lack of innovation in service delivery. Therefore, adaptive, responsive, and collaborative leadership is essential to achieving effective and sustainable public service governance at the sub-district level.